Nuclear power plant safety assessment and accident management: Practice in Sweden and computerized decision support systems - Frid, Wiktor (Computer Assisted Methods in Engineering and Science, 2002)
The methods of nuclear power plant safety assessment and accident management used in Sweden and selected computerized decision support systems are briefly described. The defense-in-depth strategy, which comprises three elements, namely prevention, protection and mitigation, is essential for keeping the fission product barriers intact. The safety assessment program, which focuses on prevention of incidents and accidents, has three main components: periodic safety reviews, probabilistic safety analysis and analysis of postulated disturbances and accident progression sequences. Even if prevention of accidents is the first priority, it is recognized that accidents involving severe core damage, including core melt, may nevertheless occur. Therefore, measures are required to achieve reasonable capability to manage such accidents. Emergency Operating Procedures and Severe Accident Management Guidelines are the vital components of the Accident Management System. Computerized decision support systems, to be used during normal, disturbed and accident states of a plant are expected to play increasingly important role in safety assessment and accident management, including support in rapid evaluation of possible radioactive releases in the event of a severe accident.